United Way CEO to lead YMCA of the USA. Issue 385 (12th September 2021) - Unknown
Abstract : YMCA of the USA has named Suzanne McCormick its next president and chief executive officer. McCormick—who will be the 15th person and first woman to lead the Y in the United States—brings more than 27 years of experience as a senior and executive leader in nonprofit organizations to the role, most recently serving as U.S. President of United Way Worldwide and a member of their global management team.